Seroprevalence of Bovine ephemeral fever virus in Gujarat State of India - Sushil Kumar Mohapatra; Bharat Singh Chandel; Mehulkumar Dharmabhai Shrimali; Husen R Parsani; Sandipkumar Sureshbhai Patel; Harsad C Chauhan; Kishan Kumar Sharma; Arunkumar Chaturbhai Patel (Veterinaria Italiana, 2023)
Bovine ephemeral fever (BEF) virus (BEFV) is an arthropod borne virus that causes bovine ephemeral fever or three‑day sickness in cattle and buffaloes. This is the first report on seroprevalence of BEF in cattle and buffaloes in Gujarat, India. Total of 92 animals, 78 cattle and 14 buffaloes from three regions (districts) of Gujarat state of India, were screened for the presence of anti‑BEF antibodies. A total of 27 out of 92 animals were found positive and overall seroprevalence detected was 29.34% (95% CI 20.0‑38.6%). A total of 19 out of 78 cattle and 8 out of 14 buffalo’s samples were found positive BEFV antibodies. Species‑wise seroprevalence in cattle and buffaloes was 24.35% (95% CI 14.8‑33.8%) and 57.1% (95% CI 31.2‑83.0%), respectively. There was a statistically significant (p < 0.05) species effect based on the seroprevalence. In cattle, location‑wise seroprevalence was observed to be 26.82% (95% CI 13.2‑40.3%) and 21.62% (95% CI 8.3‑34.8%) in Navsari and Banaskantha districts, respectively. The effect of location is not statistically significant (p < 0.05). Cytopathic effect of Vero cells was characterized by rounding, granulation of the cytoplasm within 48‑72 hrs of post infection. This was the first report demonstrating the presence of BEFV in Gujarat state.